Efficacy of iron-supplement bars to reduce anemia in urban Indian women: a cluster-randomized controlled trial. Issue 3 (18th January 2017) - Mehta, Rajvi; Platt, Alyssa C; Sun, Xizi; Desai, Mukesh; Clements, Dennis; Turner, Elizabeth L
ABSTRACT: Background: India's high prevalence of iron-deficiency anemia has largely been attributed to the local diet consisting of nonheme iron, which has lower absorption than that of heme iron. Objective: We assessed the efficacy of the consumption of iron-supplement bars in raising hemoglobin concentrations and hematocrit percentages in anemic (hemoglobin concentration <12 g/dL) Indian women of reproductive age. Design: The Let's be Well Red study was a 90-d, pair-matched, cluster-randomized controlled trial. A total of 361 nonpregnant women (age 18–35 y) were recruited from 10 sites within Mumbai and Navi Mumbai, India. All participants received anemia education and a complete blood count (CBC). Random assignment of anemic participants to intervention and control arms occurred within 5 matched site-pairs. Intervention participants received 1 iron-supplement bar (containing 14 mg Fe)/d for 90 d, whereas control subjects received nothing. CBC tests were given at days 15, 45, and 90. Primary outcomes were 90-d changes from baseline in hemoglobin concentrations and hematocrit percentages. Linear mixed models and generalized estimating equations were used to model continuous and binary outcomes, respectively. Results: Of 179 anemic participants, 136 (76.0%) completed all follow-up assessments (65 intervention and 71 control participants). Baseline characteristics were comparable by arm. Mean hemoglobin and hematocrit increases after 90 d were greater for intervention than for control participants [1.4 g/dL (95% CI: 1.3, 1.6 g/dL) and 2.7% (95% CI: 2.2%, 3.2%), respectively]. The anemia prevalence at 90 d was lower for intervention (29.2%) than for control participants (98.6%) (OR: 0.007; 95% CI: 0.001, 0.04). Conclusions: The daily consumption of an iron-supplement bar leads to increased hemoglobin concentrations and hematocrit percentages and to a lower anemia prevalence in the target population with no reported side effects. This intervention is an attractive option to combat anemia in India. This trial was registered at clinicaltrials.gov as NCT02032615.